Agriculture and biodiversity: a review. Issue 2 (3rd July 2017) - Dudley, Nigel; Alexander, Sasha
Abstract: Agriculture is the largest contributor to biodiversity loss with expanding impacts due to changing consumption patterns and growing populations. Agriculture destroys biodiversity by converting natural habitats to intensely managed systems and by releasing pollutants, including greenhouses gases. Food value chains further amplify impacts including through energy use, transport and waste. Reducing the food system's toll on biodiversity is a critical challenge. The 'sparing or sharing' debate contrasts two response pathways: intensifying agriculture to release other land for protection versus biodiversity-friendly farming over larger areas. Most conservation policies focus on intensification and set-aside but recent research challenges these assumptions. The Global Land Outlook of the UN Convention to Combat Desertification highlights how modern farming is undermining the sustainability of large land areas. Intensification has not solved the biodiversity crisis and has often made it worse. Effective responses must involve both producers and consumers, and require a mixture of conservation, sustainable management and restoration. Agricultural land serves many purposes beyond food production and mechanisms are needed to pay farmers for wider stewardship of land resources. A multifunctional landscape approach balances different needs at a landscape scale while incorporating site-level specificity on land use, demand, and condition. At the same time, consumers play a critical role in reducing unsustainable food waste. Many of the techniques and strategies for biodiversity-friendly farming systems exist; the challenge is to bring them to scale.